Preliminary Studies on the Development of Meat Balls - JO Igene; KS Akinjobi; SE Evivie (Journal of Applied Sciences and Environmental Management)
The increasing level of urbanization in Nigeria calls for development of improved versions of convenient food products. Meat ball is a value-added meat product made from beef. Three different types of meat balls: Cured Spiced Fried Ball (CSFB), Uncured Spiced Fried Ball (USFB) and Uncured Unspiced Fried Ball (UUFB) were developed all from beef, with variation in spices used and weighing from 17.67g to 18.03g respectively. The three products were evaluated by sensory evaluation panel. The three samples were tested for significant difference in taste, colour and overall likeness. The result showed that there was significant difference between the colour of CSFB and the other two samples (USFB and UUFB) (p<0.05) with CSFB rated highest. There was however no significant difference in the taste of the three samples (p>0.05). Analysis of overall likeness revealed that UUFB was significantly preferred to CSFB and USFB. The UUFB sample was rated highest in terms of overall likeness and may economically complement some of the existing popular meat-based snacks in Nigeria. The significance of the study is discussed. @JASEM